Pengaruh Intellectual Capital Terhadap Profitabilitas Pada Perusahaan Plastik Dan Kemasan Yang Terdaftardi Bursa Efek Indonesia - Seprida Hanum Harahap; Nurjannah Nurjannah (Jurnal Riset AKuntansi dan Bisnis, 2020)
This research was conducted with the aim of knowing the effect of Value Added Human capital, Value Added Capital Employed and Structural Capital Value Added on Return On Assets in plastic and packaging companies listed on the Indonesia Stock Exchange, both partially and simultaneously. The population in this study were all plastic and packaging companies listed on the Indonesia Stock Exchange, while the samples that met the criteria for sampling were observations carried out for five years and as many as six plastic and packaging companies listed on the Indonesia Stock Exchange. This research approach uses associative research. Data collection techniques in this study using documentation techniques. and the analysis technique used is multiple linear regression analysis, hypothesis testing and the coefficient of determination. The results showed that the independent variables in this study had a simultaneous effect on Return On Assets. Meanwhile, partial testing proves that the variables of Value Added Human capital and Value Added Capital employed have a significant effect on Return on Assets, while partially proves that the Structural Capital Value Added variable has no significant effect on Return on Assets in plastic and packaging companies listed on the Indonesia Stock Exchange.